Recent advances in harnessing biolubricants to enhance tribological performance and environmental responsibility – Bibliometric review (2015–2024) - Nugroho, Agus; Muhammad, Kozin; Bo, Zhang; Rizalman, Mamat; Mohd Fairusham, Ghazali; Muhammad Prisla, Kamil; Prabowo, Puranto; Diah Ayu Fitriani, .; Siti Amalina Azahra, .; Kusuma Putri, Suwondo; Putri Sayyida Ashfiya, . (Elsevier Ltd, 2024)
The necessity of conducting research on biolubricants arises from the urgent need to develop sustainable alternatives to conventional petroleum-based lubricants, which contribute to environmental degradation and carbon emissions. As biolubricants offer eco-friendly lubrication solutions, exploring their development and performance is essential to advancing sustainable technologies and achieving global net zero emissions targets. This paper aims to comprehensively plot scientific research outputs on biolubricant manufacturing and recent developments using a quantitative review technique known as bibliometric analysis. The 1000 publications were extracted from the Web of Science database and evaluated with the VOSviewer software. The study examines biolubricants' ability to support sustainability efforts, particularly through their lubrication properties, alignment with Sustainable Development Goals (SDGs), and enhancement with nanomaterials. It also identifies future trends and addresses biolubricants' limitations. The research highlights the significance of the field, with leading journals such as Industrial Crops and Products (34 articles), Tribology International (31 articles), and the Journal of Cleaner Production (29 articles) contributing extensively. The citations and document correlations analysis reveals 742 articles, grouped into 182 publication clusters, showcasing a robust network of influential research. Ongoing bibliometric evaluation is critical for identifying key developments, gaps, and opportunities in sustainable lubrication technologies.